Genome‐wide identification, evolution, and expression analysis of RNA‐binding glycine‐rich protein family in maize. Issue 10 (13th July 2014) - Zhang, Jianhua; Zhao, Yanxin; Xiao, Hailin; Zheng, Yonglian; Yue, Bing
Abstract The RNA‐binding glycine‐rich protein (RB‐GRP) family is characterized by the presence of a glycine‐rich domain arranged in (Gly)n‐X repeats and an RNA‐recognition motif (RRM). RB‐GRPs participate in varied physiological and biochemical processes especially in the stress response of plants. In this study, a total of 23 RB‐GRPs distributed on 10 chromosomes were identified in maize (Zea mays L.), and they were divided into four subgroups according to their conserved domain architecture. Five pairs of paralogs were identified, while none of them was located on the same chromosomal region, suggesting that segmental duplication is predominant in the duplication events of the RB‐GRPs in maize. Comparative analysis of RB‐GRPs in maize, Arabidopsis (Arabidopsis thaliana L.), rice (Oryza sativa L.), and wheat (Triticum aestivum) revealed that two exclusive subgroups were only identified in maize. Expression of eight ZmRB‐GRPs was significantly regulated by at least two kinds of stresses. In addition, cis‐elements predicted in the promoter regions of the ZmRB‐GRPs also indicated that these ZmRB‐GRPs would be involved in stress response of maize. The preliminary genome‐wide analysis of the RB‐GRPs in maize would provide useful information for further study on the function of the ZmRB‐GRPs.